The Political Budget Cycle is Where You Can't See It: Transparency and Fiscal Manipulation - James E. Alt; David Dreyer Lassen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2005)
We investigate the effects of fiscal transparency and political polarization on the prevalence of electoral cycles in fiscal balance. The recent political economy literature on electoral cycles identifies such cycles mainly in weak and recent democracies. In contrast, we show, conditioning on a new index of institutional fiscal transparency, that electoral cycles in fiscal balance are a feature also of advanced industrialized economies. Using a sample of nineteen OECD countries in the 1990s, we identify a persistent pattern of electoral cycles in low(er) transparency countries, while no such cycles can be observed in high(er) transparency countries. Furthermore, we find, in accordance with recent theory, that electoral cycles are larger in more politically polarized countries.
Keywords: D72; E62; H62; 330; fiscal transparency; political polarization; fiscal policy; budget deficits; political budget cycles; electoral policy cycles; Politischer Konjunkturzyklus; Finanzpolitik; Haushaltsdefizit; OECD-Staaten; Fiskalische Transparenz